1999
DOI: 10.1037/0735-7036.113.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of the hiding response to cat odor in rats (Rattus norvegicus).

Abstract: Cat odor-induced hiding was examined in rats (Rattus norvegicus) using an apparatus with a "hide box" at one end and a piece of a worn cat collar at the other end. Rats spent most of their time hiding on exposure to the cat collar, but this response gradually habituated over repeated daily exposures. Hiding was reversed by administering the anxiolytic drug midazolam (0.375 mg/kg). Rats showed increased anxiety on the elevated plus-maze after exposure to the collar. This response was absent in habituated rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 24 publications
3
52
1
3
Order By: Relevance
“…Some authors concluded that habituation did not follow repeated presentation of life-threatening stimuli, such as a predator odor [31]. However, other experiments showed responses that did habituate with prolonged exposure [14]. In addition, sensitization to predator odor has been described [18]; a robust increase in defensive responses was recorded after long-term exposure to predator odor.…”
Section: Introductionmentioning
confidence: 96%
“…Some authors concluded that habituation did not follow repeated presentation of life-threatening stimuli, such as a predator odor [31]. However, other experiments showed responses that did habituate with prolonged exposure [14]. In addition, sensitization to predator odor has been described [18]; a robust increase in defensive responses was recorded after long-term exposure to predator odor.…”
Section: Introductionmentioning
confidence: 96%
“…Adult rats display a variety of behavioral responses such as withdrawal and immobility (Blanchard & Blanchard, 1989;Dielenberg & McGregor, 1999) that allow them to avoid predation. However, predation is not restricted to adulthood.…”
mentioning
confidence: 99%
“…Likewise, 5 day treatment group showed indifferent results from the non-traumatized control group in our study. It was previously reported that habituation took place on the 5th day in a predator stress model where worn cat collar was used 20 min per day for extinction training (Dielenberg and McGregor, 1999). Similarly in our study this effect is likely to be caused by the nature of predator stress model rather than tolerance.…”
Section: Discussionmentioning
confidence: 44%